2015
DOI: 10.1186/s12913-015-1211-7
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture in cardiovascular care in Chinese hospitals: a descriptive cross-sectional study

Abstract: BackgroundOrganizational learning, the process by which a group changes its behavior in response to newly acquired knowledge, is critical to outstanding organizational performance. In hospitals, strong organizational learning culture is linked with improved health outcomes for patients. This study characterizes the organizational learning culture of hospitals in China from the perspective of a cardiology service.MethodsUsing a modified Abbreviated Learning Organization Survey (27 questions), we characterized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
2
7
0
2
Order By: Relevance
“…Close communication and collaboration between teams enabled timely re ection and sharing of problems and experiences during implementation, and made the implementation process more effective, similar ndings were found in a study of cardiovascular care in Chinese hospitals [19]. This multidisciplinary approach was emphasized in other studies of neonatal EBI implementation including family centered care and developmental care [15,21] the importance of multidisciplinary teamwork is not unique to China and can be found in other studies [22,23].…”
Section: Factors Perceived To Have a Strong Effectsupporting
confidence: 58%
“…Close communication and collaboration between teams enabled timely re ection and sharing of problems and experiences during implementation, and made the implementation process more effective, similar ndings were found in a study of cardiovascular care in Chinese hospitals [19]. This multidisciplinary approach was emphasized in other studies of neonatal EBI implementation including family centered care and developmental care [15,21] the importance of multidisciplinary teamwork is not unique to China and can be found in other studies [22,23].…”
Section: Factors Perceived To Have a Strong Effectsupporting
confidence: 58%
“…Respecto al liderazgo, se encontró que promover el cambio de la co tiene relación con que a través de este se refuercen los aprendizajes (Yin et al, 2015), y como un promotor de la adopción de medidas relativas a la implementación de sistemas de gestión requeridos para que el trabajo funcione de mejor modo (Williams, Glisson, Hemmelgarn y Grenn, 2017). En su calidad de liderazgo transformacional, este tipo de liderazgo podría conducir a pequeñas organizaciones a aportar al desarrollo de un país y ser competitivas, siempre y cuando impliquen orientación empresarial (Widianto y Harsanto, 2017).…”
Section: Dos Caminos Para Pensar La Intervención En Cultura Organizacionalunclassified
“…Interlaminar approach effectively simplifies the operation and improves the safety of surgical treatment, but it may cause nerve root traction ( 10 ), leading to nerve root injury in patients. If the local anesthesia or intraspinal epidural anesthesia is used, the intraoperative pain and discomfort will be produced ( 11 ). In order to improve the comfort of patients, studies have reported that it is considered to adopt general anesthesia in surgical treatment ( 12 ).…”
Section: Discussionmentioning
confidence: 99%